2012
DOI: 10.3141/2318-13
|View full text |Cite
|
Sign up to set email alerts
|

Development of Web-Based Parent Support Program to Improve Quantity, Quality, and Diversity of Teens’ Home-Based Practice Driving

Abstract: The purpose of this paper is to describe the development of a web-based program, the teen driving plan (TDP), for the parents of teen drivers and the results of a process evaluation to determine whether this intervention can be used as intended for the target population. The TDP is designed to promote parents’ facilitation of their teens’ home-based practice driving to increase the quantity, quality, and diversity of teens’ practice. The core functionality of the program centers on encouraging parents to plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Additionally, important information, including content on more advanced driving skills, should be provided early in the learner period when engagement is greatest, encouraging continued learning as part of logging practice drives, and incorporating monitoring software for further personalisation to meet family needs. Additionally, consideration should be given to providing access to the learning component of TDP prior to the learner phase of licensure, a recommendation given by participants in the process evaluation study 15. A mobile version of TDP might be preferred by families who rely on drives of convenience to practice driving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, important information, including content on more advanced driving skills, should be provided early in the learner period when engagement is greatest, encouraging continued learning as part of logging practice drives, and incorporating monitoring software for further personalisation to meet family needs. Additionally, consideration should be given to providing access to the learning component of TDP prior to the learner phase of licensure, a recommendation given by participants in the process evaluation study 15. A mobile version of TDP might be preferred by families who rely on drives of convenience to practice driving.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous TDP process evaluation study, we learned that either the teen or the parent or both could be engaged in the use of TDP on their own or on behalf of the dyad 15. Thus, TDP use metrics will be reported on a dyad level.…”
Section: Methodsmentioning
confidence: 99%
“…TeenDrivingPlan was a web-based program for parents of permit holders with three core components: (1) brief videos on how to structure practice activities across a variety of driving environments; (2) an interactive web-based planner to promote supervised driving; and (3) logging and rating of practice hours and driving behaviors [24, 45-47]. The intervention draws from several theoretical frameworks, including the Integrative Model of Behavior Change [48], and was designed to increase the quantity, quality, and variety of supervised practice.…”
Section: Resultsmentioning
confidence: 99%
“…However, research has shown gaps in parent success in this role as well as in our knowledge about specific parent attributes and parent-teen interactions that have the most beneficial effect on teen drivers' safety [20]. Parents generally exhibit poor monitoring and control of teens' risky driving behaviors, often fail to clearly define driving rules and expectations [13,21-23], have varying levels of engagement in helping their teens mature to independent drivers, and face challenges in knowing how to promote safe, skilled driving [24-27]. …”
mentioning
confidence: 99%
“…Studies measuring practice diversity are rare, and have relied self-reported assessment of practice in different driving environments (Mirman, Lee et al 2012, Mirman, Albert et al 2014). Currently, the extent to which practice is repetitive, occurring on the same types of roads during the same time of day, or provides exposure to a variety of driving conditions is unknown.…”
Section: Introductionmentioning
confidence: 99%